Muḥâwalât Taysîr al-Naḥw ‘Inda al-Mujaddidîn Li Tashîl al-‘Arabiyah li al-Nâṭiqîna Bighairihâ - Nasution, sahkholid; Suharmon, Suharmon (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Purpose- This study aims to present information about: 1). The problem of learning nahwu, and 2). The efforts of the Islamic scholars in simplifying the nahwu material to be more easily learned, especially for beginners and non-Arabic speakers.  Design/Methodology/Approach- This paper is a conceptual analysis using descriptive analysis methods. The data were obtained through library research.  Findings- It can be concluded that the main factor making nahwu material difficult to be learned is the philosophical and layered analysis of i'rab , while this practical analysis is considered not to make a lot of positive contributions in understanding a text, especially for being fluent in speaking Arabic.  Research  Limitation/Implications- Therefore, the solution is not to learn the theory âmil; theory of  illat tsawâni and tsawâlits; theory of qiyâs, and the theory of al-tamârîn al-muftaridhah particularly for novice students of non-Arabic speakers.  Keywords: Non-Arabic speakers, i’rab, âmil; ‘illat tsawâni, tsawâlits; qiyâs, al-tamârîn al-muftaridhah.